Inhibition of Paenibacillus larvae and Ascosphaera apis by Bacillus subtilis isolated from honeybee gut and honey samples - Sabate, Daniela Constanza (2009)
Three Bacillus strains isolated from honey samples and bee gut were pre-selected for their in vitro antimicrobial activity against Paenibacillus larvae and Ascosphaera apis, important honeybee pathogens. The analysis of their 16S rRNA sequences revealed that C4, M1 and G2III strains belong to the subtilis species. Surfactin synthesis was verified by IR spectroscopy and HPLC studies. Surfactin inhibited P. larvae but it failed to affect A. apis. Vegetative cells of P. larvae were affected as soon as they came in contact with the surfactin sample; two orders of magnitude less in log scale were recorded. Optimal surfactin production was observed in MEL medium, a broth with molasses as the only carbon source. Bacillus subtilis G2III strain exhibited the highest levels of surfactin synthesis in BHI and MEL broths: 1391 AU/ml and 2782 AU/ml, respectively. Since only A. apis inhibition was observed when cell suspensions were assayed, we suspect that there may be an antimycotic compound within cells. The co-production of surfactin and a fungicide by these strains might biologically control bee pathogens in apiculture. © 2009 Elsevier Masson SAS. All rights reserved.